2018
DOI: 10.3390/app8112231
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ageing on Chemical and Mechanical Properties of Asphalt Mortar

Abstract: Asphalt mortar is a mixture of bitumen, filler, and sand. Mortar plays an important role in asphalt mixtures as it serves as the adhesive between the coarser aggregates. Due to the effect of bitumen ageing, the chemical and mechanical properties of asphalt mortar evolve with time. The mortar becomes more brittle and prone to cracking, thus leading to inferior pavement performance. In this study, Fourier transform infrared (FTIR) spectrometry was used to quantify changes in the chemical functional groups relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As the asphalt binder generated no evident characteristic fingerprint within the wavenumber range of 1800-2400 cm -1 , the absorption peak within this range was not reflected in the spectrum. According to previous research results, the carbonyl index and sulfoxide index were used as evaluation indices of the aging degree of asphalt samples [43][44][45]. The carbonyl index and sulfoxide index can be calculated with Eqs.…”
Section: Attenuated Total Reflectance Fourier Transformation Infrared...mentioning
confidence: 99%
“…As the asphalt binder generated no evident characteristic fingerprint within the wavenumber range of 1800-2400 cm -1 , the absorption peak within this range was not reflected in the spectrum. According to previous research results, the carbonyl index and sulfoxide index were used as evaluation indices of the aging degree of asphalt samples [43][44][45]. The carbonyl index and sulfoxide index can be calculated with Eqs.…”
Section: Attenuated Total Reflectance Fourier Transformation Infrared...mentioning
confidence: 99%
“…Furthermore, long-term characterization using FTIR analysis in the range of wavenumbers from 4000 to 600 cm −1 . Long-term asphalt aging is indicated by the formation of carbonyl groups (-C=O) at the wave number 1700 cm −1 and sulfoxide (-S=O) at the wave number 1030-1070 cm −1 [42,43].…”
Section: Ft-ir Modified Asphalt Before and After Ltoamentioning
confidence: 99%
“…While the group at wave number 1060 cm −1 shows the sulfoxide (S-O) groups of asphalt [42][43][44]. Naturally, asphalt has a sulfoxide group because asphalt contains a certain amount of sulfur.…”
Section: Ft-ir Modified Asphalt Before and After Ltoamentioning
confidence: 99%
“…Therefore, some scholars analyzed the influence of time and temperature on asphalt aging and found that the longer the aging time and the higher the temperature, the deeper the aging of asphalt and the worse the paving performance of asphalt mixes [23][24][25][26]. At the same time, in order to further understand the aging process of asphalt, it was found through microscopy that aging causes changes in the chemical functional groups of asphalt, which results in the nanomorphology and micromechanical properties of asphalt being affected [27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%